FLOWPATH 2019 - NATIONAL MEETING ON HYDROGEOLOGY (Ledizioni, 2019)
FLOWPATH 2019, the 4th National Meeting on Hydrogeology, was held in Milan from 12th to 14th June 2019. According to the aim of the previous Editions of FLOWPATH, held in Bologna (2012), Viterbo (2014) and Cagliari (2017), the conference is an opportunity for Italian hydrogeologists to exchange ideas and knowledge on different groundwater issues. The objectives of the conference are: - To promote dialogue and exchange of scientific knowledge among young hydrogeologists; - To deepen the theoretical and practical aspects of our understanding on groundwater; - To update all the stakeholders, researchers and professionals on recent challenges in the hydrogeological sciences; - To encourage researchers, professionals and administrators to contribute to the improvement of water resources management.